1997
DOI: 10.1590/s0101-20611997000400026
|View full text |Cite
|
Sign up to set email alerts
|

The Generalized Maximum Likelihood Method Applied to High Pressure Phase Equilibrium

Abstract: The generalized maximum likelihood method was used to determine binary interaction parameters between carbon dioxide and components of orange essential oil. Vapor-liquid equilibrium was modeled with Peng-Robinson and Soave-Redlich-Kwong equations, using a methodology proposed in 1979 by Asselineau, Bogdanic and Vidal. Experimental vapor-liquid equilibrium data on binary mixtures formed with carbon dioxide and compounds usually found in orange essential oil were used to test the model. These systems were chosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is also shown that, for some data sets, parameter values published in the DECHEMA VLE Data Collection correspond to a local minimum. The maximum likelihood principle (MLE) has been applied by several researchers for the correlation of vapor-liquid equilibrium data under atmospheric pressure up to high pressure, such as Cardozo-Filho et al (1997). These authors applied MLE to the modeling of the CO 2 + ethanol binary system (Yoon et al, 1993;Suzuki et al, 1990) with the Peng-Robinson equation of state, and their results are better tan those with the least squares error (LS) method.…”
Section: Validationmentioning
confidence: 99%
“…It is also shown that, for some data sets, parameter values published in the DECHEMA VLE Data Collection correspond to a local minimum. The maximum likelihood principle (MLE) has been applied by several researchers for the correlation of vapor-liquid equilibrium data under atmospheric pressure up to high pressure, such as Cardozo-Filho et al (1997). These authors applied MLE to the modeling of the CO 2 + ethanol binary system (Yoon et al, 1993;Suzuki et al, 1990) with the Peng-Robinson equation of state, and their results are better tan those with the least squares error (LS) method.…”
Section: Validationmentioning
confidence: 99%